Fully Adaptive Clutter Suppression for Airborne Multichannel Phase Array Radar Using a Single A/D Converter. (17th August 2010) - Madurasinghe Madurasinghe, Dan Dan; Shaw Shaw, Andrew P. Andrew P.
Abstract : This study considers an airborne multichannel phase array radar consisting of an analog phase shifter on each channel, where the sum channel (output) is digitised using a single A/D converter. Generally for such a configuration, the array weights are predetermined for each transmit/receive direction and are nonadaptive to the clutter. In order to achieve any adaptivity to the environment, the convention is to split the array into at least two subgroups and implement two analogs to digital converters. A single A/D-based software solution (numerically stable, robust) is proposed to achieve the full sidelobe adaptation to clutter. The proposed algorithm avoids these engineering complications involved in implementing multiple A/Ds for radar applications while maintaining the same desired performance. As a large number of airborne radar platforms already exist worldwide, the possible applications of this proposed fully adaptive upgrade as a software solution can be huge.